2011
DOI: 10.1074/jbc.m110.165977
|View full text |Cite
|
Sign up to set email alerts
|

SKP2 Oncogene Is a Direct MYC Target Gene and MYC Down-regulates p27KIP1 through SKP2 in Human Leukemia Cells

Abstract: SKP2 is the ubiquitin ligase subunit that targets p27 KIP1(p27) for degradation. SKP2 is induced in the G 1 -S transit of the cell cycle, is frequently overexpressed in human cancer, and displays transformation activity in experimental models. Here we show that MYC induces SKP2 expression at the mRNA and protein levels in human myeloid leukemia K562 cells with conditional MYC expression. Importantly, in these systems, induction of MYC did not activate cell proliferation, ruling out SKP2 up-regulation as a cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
79
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(87 citation statements)
references
References 70 publications
8
79
0
Order By: Relevance
“…Aberrant Skp2 signaling has been implicated as a driving event in tumorigenesis. Overexpression of Skp2 was frequently observed in numerous human cancers, such as ovarian, colorectal, gastric, prostate, lung, sarcoma, breast and other cancers (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). These observations suggest that Skp2 may contribute to the development of human cancers.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Aberrant Skp2 signaling has been implicated as a driving event in tumorigenesis. Overexpression of Skp2 was frequently observed in numerous human cancers, such as ovarian, colorectal, gastric, prostate, lung, sarcoma, breast and other cancers (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). These observations suggest that Skp2 may contribute to the development of human cancers.…”
Section: Introductionmentioning
confidence: 85%
“…However, the expression and role of HBXIP in ovarian cancer cells is poorly understood. Many studies have shown that overexpression of Skp2 is observed in a variety of human cancers, including ovarian cancer, gastric cancer, colorectal cancer, prostate cancer, sarcoma, breast cancer, lung cancer, pancreatic cancer and other cancers (15,26). In addition, Skp2 has an estab- lished role in the migration of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…The cell cycle is regulated by various factors, including cyclin, cyclin-dependent kinases (CDKs) and CDK interacting protein (cip)/kinase inhibitory protein (kip). S-phase kinase-associated protein 2 (Skp2) mainly induces the degradation of CDK inhibitors, including p21 cip1 , p27 kip1 and p57 kip2 (19)(20)(21). As an F-box protein, Skp2 is a key regulator for cell cycle progression.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, exogenous p27 kip1 expression partially antagonizes the effect of Bcr-Abl on proliferation (Albero et al, 2010;Andreu et al, 2005;Bretones et al, 2011;Jonuleit et al, 2000). By inhibiting the tyrosine kinase activity of BcrAbl with Imatinib, the half-life of p27 kip1 is increased, meaning that Bcr-Abl induces the degradation of p27 kip1 .…”
Section: Bcr-abl and The Proteasomementioning
confidence: 99%
“…Ignacio Peŕez-Roger and Mariá Pilar Albero (2011). The Proteasome as a Therapeutic Target in Chronic Myeloid Leukemia, Myeloid Leukemia -Basic Mechanisms of Leukemogenesis, Dr Steffen Koschmieder (Ed.…”
Section: How To Referencementioning
confidence: 99%